Os impactos da lei brasileira de inclusão na capacidade negocial da pessoa com deficiência - Xexéo, Leonardo Monteiro (2019)
The present study aims to analyze the effects of the Brazilian Inclusion Law on the negotiation capacity of the disabled person. The study starts with the questioning of whether or not a micro system is in place to protect the rights of people with disabilities. For this purpose part of the lessons of Niklas Luhmann. With the result of this investigation, the impact of this finding in the legal system will be verified, especially in the institutes of the personality, of the capacity and incapacity, that were modified by the edition of Law nº 13,146, of 2015. The focus resides in the examination of the alteration of the disability system, with the inclusion of respect for the person's will, and its impact on the legal business practiced by the mentally or intellectually disabled person